The Effect of Healthcare Infection Control Application Committee in Patients Using Urine Cateters on Cost Containtment - M. Rizky Priyanka Asepty; Asriwati Amirah; Jamaluddin Jamaluddin (Journal La Medihealtico, 2022)
The high prevalence of HAIs (Healthcare-associated Infections) is a threat to hospital services. Implementation of infection prevention and control is the biggest challenge in the arrangement of health services, especially in hospitals. HICPAC is one of the CDC guidelines that is quite recommended in reducing the incidence of infections in hospitals. This study aims to assess the effect of implementing HICPAC with a reduction in hospital costs in patients using a urine catheter at Delia Hospital in Langkat District in 2019. The type of research is quantitative with a quasi-experimental approach conducted at Delia General Hospital in Langkat District with a population of 30 patients and analyzed using Paired T Test analysis. The analysis found that there were differences in treatment costs based on secondary diagnoses before and after the HICPAC guidelines were applied. This shows that the HICPAC guidelines can significantly reduce the cost of care for patients who use urine catheters at Delia Hospital in Langkat District. So it is recommended that the HICPAC guidelines can be used integrated with the medical record so that it is easily implemented by all medical personnel in the hospital.